Identification of bio-intensive pest management (BIPM) approaches in sesame for organically managed system: Identification of bio-intensive pest management (BIPM) approaches in sesame for organically managed system - A K PANDAY; RAJANI BISEN; DWARKA; SURABHI JAIN; K N GUPTA; ROSHANI SAHU (Journal of Oilseeds Research, 2023)
The result revealed that all the bio-intensive treatments recorded significantly higher population of natural enemies as compared to control. Among the treatments, the lowest larval population of Antigastra (0.20 and 1.00 larvae/plant at 7 and 14 days after first spraying respectively) was recorded from the treatment T7 (Farmer Practices) followed by (0.33 and 1.13 larvae/plant after 7 and 14 days after first spraying respectively) treatment T3. The highest seed yield (907 kg/ha) was recorded from the treatment T6 followed by (903 kg/ha) T5, while the highest BC ratio (5.9) was received from the treatment T7 followed by (4.4) T2 and T3..